Pendampingan dan Bimbingan Kajian Fiqh di Mushola Darul Ikhsan Desa Nambangrejo Tentang Amil Zakat dan Tadarus Bagi Wanita di Bulan Ramadhan - Kholifah, Aulia Nurul; Luqman, Asaduddin; Sholeh, Moh. (Social Science Academic, 2024)
Ramadan is a special month known for focusing on the obligatory fasting, while also highlighting two key practices; tadarus and zakat. Reading the Qur'an or tadarus can be done individually or in groups to increase understanding and devotion to Allah SWT. However, the majority of traditions suggest that Muslimah should not use microphones to prevent their voices from being overheard by non-mahrams. Zakat, is a form of servitude to Allah. Zakat is a commandment of Allah that commands Muslims and Muslimahs to give part of their assets either income or crops to those entitled to receive it as a form of generosity and social responsibility with the right calculation. This research uses the literature review method from the fiqh study that is routinely held at the Darul Ikhsan Mosque in Nambangrejo Village RT.01/RW.01 every Tuesday night. Through analysis, an understanding of Ramadan customs emerges that underlines its role in promoting community development and unity.